Personalized rankings: a new ranking system for Taiwanese universities / Angela Yung-chi Hou - Hou, Angela Yung-chi (ACRULeT, Faculty of Education & UiTM Press, 2009)
Because traditional college rankings had many methodological problems a new type of user-based ranking, called “personalized college ranking” was developed in many nations in the late 1990s. The main objective of this paper, therefore, is to explore what challenges are involved in the development of current college rankings nationally and globally and how to establish a new type of ranking system. The paper starts by attempting to understand the pitfalls and criticisms of college rankings. Based on the analysis of five major personalized rankings, it outlines strategies and pathways for establishing personalized college rankings in Taiwan